Mediating Factors of the Association Between Shyness and Generalized Pathological Internet Use in Chinese University Students. - Tian, Yu; Si, Yingdong; Meng, Weixuan; Bian, Yulong; Han, Piguo; Hu, Jie; Wang, Peng; Gao, Fengqiang (International Journal of Mental Health & Addiction, 2019)
This study examined the associations between shyness and generalized pathological Internet use (GPIU) to identify the possible mechanisms underlying how shyness influences GPIU through the mediating effect of interpersonal relationships, loneliness, and maladaptive cognitions. We also determined whether a gender difference exists in these underlying mechanisms. A total of 1621 Chinese undergraduate students, with a mean age of 21.68 (standard deviation [SD] = 2.01 years) years, completed a questionnaire including scales for shyness, interpersonal relationships, loneliness, maladaptive cognitions, and GPIU. The results of structural equation modeling (SEM) analysis indicated that (i) shyness could positively influence GPIU from maladaptive cognitions; (ii) shyness could positively influence GPIU through loneliness → maladaptive cognitions; (iii) shyness could positively influence GPIU through interpersonal relationships → loneliness → maladaptive cognitions; and (iv) although the association patterns between shyness and GPIU were similar for both groups, the strength of these associations was stronger for male students. Moreover, the interventions for GPIU and the implications for future studies are discussed.